Pengaruh Konten Media Sosial Instagram pada Akun @selatan.florist terhadap Minat Beli Followers: Pendekatan Elaboration Likelihood Model - Retno Wulandari; Budi Santoso (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
The rapid advancement of technology has pushed business actors to rely on social media as their primary promotional channel. On the @selatan.florist account, several obstacles were identified in content production — particularly in feeds, stories, and reels — concerning visual appeal, upload consistency, and the depth of informative value delivered to the audience. This study examines the extent to which social media content produced by @selatan.florist affects followers' purchase intention. The Elaboration Likelihood Model (ELM) serves as the theoretical lens, explaining how individuals process persuasive messages and form attitudes in response. A quantitative methodology was applied, with a structured questionnaire distributed to 152 respondents who follow the @selatan.florist account. Simple linear regression analysis reveals a statistically significant influence of social media content on purchase intention. The R² value of 66.3% indicates that visual aesthetics and informational depth in the account's content are decisive factors in converting audience attention into purchasing behavior.